Photovoltaic power stations: an opportunity to promote European semi-natural grasslands? - Lambert, Quentin; Bischoff, Armin; Enea, Morgane; Gros, Raphael (Frontiers in Environmental Science, 2023)
European semi-natural grasslands are particularly species rich and provide many ecosystem services but depend on extensive land management. Today, these ecosystems are highly threatened by land abandonment, land use intensification and habitat destruction. The increasing construction of solar parks may contribute to habitat destruction but also provide an opportunity to restore or even create semi-natural grasslands. We studied ten solar parks along a climate gradient in Southern France to evaluate the establishment of semi-natural grasslands managed by grazing. We compared plots outside and under solar panels in terms of plant community composition, soil biodiversity and soil functioning to test whether solar panels hamper this establishment. The different microclimate under solar panels strongly affected the plant species composition and reduced the abundance of soil mesofauna and biomass of fungi and gram-negative bacteria. Outside panels, the vegetation was shaped by a climatic gradient, in particular by variations in temperature and precipitation whereas under panels variations were smaller indicating a homogenizing effect of panels on plant community composition. We found more trophic interactions between panels compared to outside and under panels suggesting a protection effect of panels between rows on the soil food web. . However, plots under panels showed the lowest number of interactions demonstrating that the strong shading had a negative effect on the plant-soil food web. Solar panels therefore reduce the plant and soil biodiversity of semi-natural grasslands and disrupt ecosystem functions. In order to improve the ecological integration of solar parks, it is thus necessary to mitigate negative effects of solar panels on biodiversity or to increase the space between panels.